Bioaccumulation of Heavy Metals Fe, Cu, and Mn in Mozambique Tilapia (Oreochromis mossambicus) from Situ Tlajung Hilir, Gunung Putri, Bogor - Widya Kartika Laksmawati; Mia Azizah; Nurlela Nurlela; Sufrizal Ihsan Latief (Journal of Biotropical Research and Nature Technology, 2026)
Freshwater ecosystems located near urban, industrial, and residential areas are vulnerable to heavy metal contamination derived from anthropogenic activities, including industrial discharge, domestic wastewater, and surface runoff. These contaminants may accumulate in aquatic organisms and potentially affect food safety when contaminated fish are consumed. This study evaluated the concentrations of iron (Fe), copper (Cu), and manganese (Mn) in the edible muscle tissue of Mozambique tilapia (Oreochromis mossambicus) collected from Situ Tlajung Hilir, Bogor Regency, Indonesia. Fish samples were obtained from three purposively selected locations representing areas influenced by community activities, industrial operations, and domestic wastewater discharge. Heavy metal concentrations were determined using Atomic Absorption Spectroscopy (AAS) following wet digestion of dried muscle tissues. The concentrations of Fe, Cu, and Mn varied among sampling locations, with Fe showing the highest accumulation, followed by Cu and Mn. Based on dry weight measurements, Fe concentrations ranged from 66.14 to 621.39 mg kg⁻¹, Cu from 0.87 to 21.27 mg kg⁻¹, and Mn from 5.14 to 6.18 mg kg⁻¹. Although numerical differences were observed among sampling locations, statistical analysis indicated that these differences were not significant, suggesting high within-site variability and limited statistical power due to the small number of biological replicates. The elevated concentrations of metals in fish muscle indicate that O. mossambicus from Situ Tlajung Hilir has accumulated Fe, Cu, and Mn, possibly reflecting the influence of surrounding anthropogenic activities. However, direct identification of contamination sources requires further analysis of water, sediment, and physicochemical parameters. These findings provide preliminary evidence of heavy metal bioaccumulation in fish from an urban freshwater ecosystem and highlight the need for continuous environmental monitoring and future human health risk assessment.